Characterization of Pseudocercospora griseola, identification of local sources of resistance and effectiveness of gene pyramiding in controlling angular leaf spot in common bean - Ddamulira, Gabriel (Makerere University, 2016)
Angular leaf spot (Pseudocercospora griseola) is a major disease of common bean (Phaseolus vulgaris L.) globally and accounts for 50% yield loss in Uganda. High levels of variety resistance to the disease would minimise yield losses. This study was conducted to; determine the distribution and variability of angular leaf spot (ALS) pathogen, identify new sources of resistance and their inheritance, and elucidate the effectiveness of pyramided genes in improving ALS resistance. A survey was conducted in ten districts of Uganda to determine the distribution of P. griseola, and angular leaf spot differential cultivars and molecular makers were used to define the variability of P. griseola. On the other hand, eighty bean genotypes were screened with four P. griseola isolates to identify new sources of ALS resistance. Futhermore crosses were made between the identified resistant source (U00297) with susceptible parents (K132, K131 and Kanyebwa) as well as other resistant parents (G5686, AND277 and Mexico 54) to generate F1, F2 and back crosses. The parents with their progenies were inoculated with P. griseola isolates 61:63, 21:39 and 17:39 to determine the inheritance of ALS resistance and allelic relationship between resistance genes. Similarly, ALS resistant genes in Mexico 54, AND277 and G5686 were pyramided into single genotypes using a cascading scheme to generate single cross (SC), triple cross (TC) and four parent cross (FPC). The SC, TC and FPC were then crossed with susceptible parents (Kanyebwa and K132) to generate F1 and F2. The F1, F2 with their parents were screened with P. griseola isolate 61: 63 to determine the effectiveness of the pyramided genes in improving ALS resistance. Results showed that angular leaf spot was widely distributed in all districts and altitudes surveyed. The highest disease incidence (68.5%) and severity (46%) were recorded in Dokolo district and the lowest incidence (29%) and severity (11.2%) in Kisoro. Both disease incidence (60%) and severity (45%) were higher in low altitude areas than incidence (33.6%) and severity (20.7%) in high altitude areas. The pathogen was highly variable with 12 pathotypes and 30 haplotypes, defined by ALS differential cultivars and molecular markers, respectively. Pathotype 17:39 and 61:63 were observed to be the most prevalent and virulent in Uganda. U00297 was resistant to all the four pathotypes and regarded as a new source of ALS resistance in Uganda. Segregation ratios of F2 populations indicated that U00297 resistance to pathotype 17:39 was conferred by a dominant gene, while digenic epistatic gene interaction was were responsible for its resistance to pathotypes 61:63 and 21:39. In addition, the dominant gene in U00297 was independent of resistance genes harboured in AND277 and G5686. The pyramided genes showed varying segregation ratios depending on the type of cross. The SC, TC and FPC crosses best fitted for 15:1, 61:3 249:7 ratios, suggesting that SC, TC and FPC segregated for two, three and four genes, respectively. The pyramided genotype (FPC) exhibited the highest level of ALS resistance to the most virulent pathotype 61:63 indicating that crosses with combined resistance genes were more effective in transferring ALS resistance to susceptible bean cultivars.